Factoriser au maximum en reperant un facteur commun (quand je met ^2 c'est au carre)
A=3x(x-5)-x
B=x^2 (x+4)-2x(x+4)
C=(x-3)^2 -2(x-3)(2x-1)
D=2x(2x+1)-3(2x+1)
E=4x(-3x+5)-7(3x+5)
F=4x^2 (-x+3)-2x(-x+3)
G=(x+6)^2 -2(x+1)(x+6)

1

Réponses

Meilleure réponse !
2014-01-22T21:18:14+01:00
Sauf erreur de ma part
A=3x(x-5)-x
A = x(3(x-5)-1)
A = x(3x-15-1)
A = x(3x-16)
B=x^2 (x+4)-2x(x+4)
B = (x+4)(x2) - (x+4)(2x)
B = (x+4)( x2 - 2x)
B = (x+4)( x-2)(x)
C=(x-3)^2 -2(x-3)(2x-1)
C = (x-3)(x-3) - 2(x-3)(2x-1)
C = (x-3)(x-3) - 2(x-3)(2x-1)
C = (x-3)(x-3) - (x-3)(4x-2)
C = (x-3)(x-3-4x+2)
C = (x-3)(-3x-1)
D=2x(2x+1)-3(2x+1)
D = (2x+1)(2x -3)
E=4x(-3x+5)-7(3x+5)
?
F=4x^2 (-x+3)-2x(-x+3)
F = (2x)(2x)(-x+3) - 2x(-x+3)
F = (2x)(-x+3)(2x-1)
G=(x+6)^2 -2(x+1)(x+6)
G = (x+6)(x+6) - 2(x+1)(x+6)
G = (x+6)(x+6-2x-2)
G = (x+6)(-x+4)